1999
DOI: 10.1211/146080899128735289
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Delivery of Insulin Using a Bioadhesive Hydrogel Preparation Containing Lauric Acid as an Enhancer in Rats

Abstract: The rectal delivery of insulin using a bioadhesive hydrogel preparation containing various absorption enhancers was evaluated in rats. Hydrogels were prepared from acrylic block copolymers of methacrylic acid and methacrylate (Eudispert hv). Sodium salts of various fatty acids were incorporated into the hydrogels as absorption enhancers. Sodium oleic acid and 2,6‐di‐O‐methyl‐β‐cyclo‐dextrin (DM‐β‐CyD) were used as control enhancers. Rectal administration of 50 units kg−1 insulin‐loaded 7% (w/w) Eudispert hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Additional delivery sites that have been explored for their accessibility include the rectal, vaginal and ocular mucosas. Protein delivery via the rectal mucosa has been investigated by Uchida et al (1999). An advantage of rectal delivery is the avoidance of enzymatic degradation since there can be direct protein absorption by the lymphatic system (Owens et al, 2003).…”
Section: Drug Delivery Routesmentioning
confidence: 99%
“…Additional delivery sites that have been explored for their accessibility include the rectal, vaginal and ocular mucosas. Protein delivery via the rectal mucosa has been investigated by Uchida et al (1999). An advantage of rectal delivery is the avoidance of enzymatic degradation since there can be direct protein absorption by the lymphatic system (Owens et al, 2003).…”
Section: Drug Delivery Routesmentioning
confidence: 99%
“…In particular the oral route, which is the most convenient and easy medication, is the less suitable for protein molecules. Most peptide drugs show very low oral activity as a consequence of the degradation by gastrointestinal tract enzymes and the poor permeability of the intestinal mucosa. , Alternative medications, such as nasal, pulmonary, , rectal, buccal, vaginal, and transdermal, have been investigated. But it has been shown that protease activities in the homogenates of the nasal, buccal, rectal, and vaginal mucosa of rabbits are substantial and quite comparable to those found in the intestinal mucosa …”
Section: Introductionmentioning
confidence: 99%